2020
DOI: 10.3390/geosciences10060242
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Pollution in the Tourism Environment: A Literature Review

Abstract: Cadmium is a highly-toxic metal, and, its environmental occurrence and human exposure consequently deserve close attention. The insight into the relationships between cadmium and tourism relations has deepened during the past three decades and the research into this relationship is reviewed. For this purpose, 83 relevant publications (mainly articles in international journals) were analyzed. It was found that investigation of Cd in the tourism environment took place in all continents (except Antarctica) and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 142 publications
0
27
0
2
Order By: Relevance
“…Plants, due to being sessile and directly dependent on the soil, frequently experience the harmful effects of these heavy metals [5]. Among the heavy metals, cadmium is a highly toxic, non-degradable pollutant that significantly impacts living organisms [6][7][8]. It is discharged into the environment from metalworking industries, power stations, heating systems, and urban traffic [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…Plants, due to being sessile and directly dependent on the soil, frequently experience the harmful effects of these heavy metals [5]. Among the heavy metals, cadmium is a highly toxic, non-degradable pollutant that significantly impacts living organisms [6][7][8]. It is discharged into the environment from metalworking industries, power stations, heating systems, and urban traffic [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the proposed model as a valuable tool to be used by monitoring programs assessing environmental quality parameters of coastal waters under the influence of maritime traffic. Moreover, the proposed indicator is specifically recommended to be used in areas with high heterogeneity in the types of vessels, as is often seen in Latin American coastal areas [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, maritime traffic (MT) is negatively affecting marine environments [2,3]. In fact, ship and boat traffic produce water contamination by oil [4][5][6], toxic metals [7,8], and several antifouling biocides [9]. In addition, atmospheric emissions contributing to the greenhouse effect are also a relevant impact related to MT [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Our results verified that there are many uncertainties to reveal the heavy metal variations within different road buffers. Further research needs to be undertaken in different habitat types and climatic regions in association with different road types and pollutants [15].…”
Section: Heavy Metal Variations Associated With Roadsmentioning
confidence: 99%
“…The road effect zone suffers from long-term accumulation of heavy metals, and these pollutants have an impact on the environment and nearby ecosystems. Some studies even focused on the relationships between cadmium pollution in view of tourism activities [15]. More studies have shown the contamination by these elements and the distribution of heavy metals in road dusts and soils [16][17][18].…”
Section: Introductionmentioning
confidence: 99%